Fundamental experiments and quantum technology applications with defect centres in diamond - Benson, Oliver (Springer Verlag, 2018)
The observation of single quantum objects has been a challenging task requiring advanced experimental techniques. With improved microscopy methodology it is nowadays possible to observe such objects in the solid state with compact setups even at room temperature. In this contribution we introduce defect centres in diamond and discuss two recent experiments. One concerns the direct observation of the quantum nature of light with not more but a single detector. The second one shows how to use defect centres as a valuable light source for quantum key distribution.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Diamond defect centre; Light quantization; Quantum information; Quantum key distribution; Single photons; Superconducting detectors